Restoration of endodontically treated teeth with major hard tissue loss - influence of post surface design on pull-out bond strength of fiber-reinforced composite posts - Koch, Andreas; Binus, Stefanie; Holzschuh, Barbara; Petschelt, Anselm; Powers, John M.; Berthold, Christine (Dental Traumatology, 2014)
The aim was to evaluate the influence of post surface design and luting system on bond strength of quartz-fiber-reinforced composite posts (QFRCPs) luted to root canal dentin.Single-rooted bovine teeth (n = 650) were randomly assigned (13 groups, n = 50), sectioned, endodontically treated, filled, and post space (length 8 mm) prepared. Custom-made plain-surfaced fiber posts (PSXRO) and (both RTD) macroretentive Macro-Lock Post Illusion X-RO (MLXRO) were inserted into the post spaces using six luting systems: Ketac Cem (KC), Fuji Plus (FP), RelyX Unicem, Multilink Primer_Multilink, Sealbond Ultima_CoreCem, and LuxaBond_LuxaCore Z. As control, a titanium post was cemented with KC. After water storage (24 h, 37°C), pull-out test was performed, followed by failure mode assessment. Bond strength was calculated in MPa and analyzed using anova, Dunnett-T3-test, and Student's t-test with Bonferroni correction.Post design and luting system significantly influenced the bond strength [MPa] (P < 0.05). Compared with the control 4.3 (1.5), all test groups exhibited higher bond strengths (P < 0.05), except for group PSXRO/KC 4.2 (1.0). The remaining bond strengths were PSXRO: FP 8.6 (1.5), RelyX Unicem 10.4 (3.4), Multilink Primer_Multilink 12.7 (3.0), SealBond Ultima_CoreCem 12.7 (3.0), LuxaBond_LuxaCore Z 15.7 (2.5), and MLXRO: KC 7.2 (2.2), FP 13.4 (2.5), RelyX Unicem 9.2 (2.9), Multilink Primer_Multilink 12.5 (4.5), SealBond Ultima_CoreCem 13.7 (4.6), LuxaBond_LuxaCore Z 20.6 (2.2). The bond strengths of MLXRO were higher than those of PSXRO when luted with KC, FP, and LuxaBond_LuxaCore Z (P < 0.05).The post surface design and luting system selection influenced the bond strength of conventionally and adhesively luted QFRCPs to bovine root canal dentin.
EVALuna2:24661